LIMPAHAN PENGARUH PELABUHAN RAJANG TERHADAP BANDAR SIBU - Norasitah, Abu (Universiti Malaysia Sarawak, (UNIMAS), 2002)
The objective of this research is to study the influence of Rajang Port onto Sibu Town. Specifically the study aims to evaluate the situation of Sibu Town before and after the construction of Rajang Port from various aspects, namely physical (that is the expansion of the town), economic (especially, contribution to town growth) and social (that is, positive and negative factors introduced or enhanced by the Rajang Port onto the town community). Secondary and primary information were collected to support the study. Secondary information were gathered from published books and articles, while primary information were obtained through observation, questionnaire and interviews. In addition, a GIS software, Are View was used to produced various levels of town maps. Information for this study were collected from three specific areas - 1 area within a radius of I to 5 kilometer from the Port; 2 area between 5 to 10 kilometer from the Port; and 3 area above 10 kilometer away from the Port. The study findings showed that the Rajang Port has had influence on Sibu Town physical, economic and sosial changes. The addition of road and the extension town border relates to physical influence. The availability of job opportunities with the existence of new businesses and industries is the Port economic contribution. With growing economy the town has improved level of urbanization, that is improved population level of living. Overall, the construction of Rajang Port has had influence upon all areas within the town center